Shear layer flame stabilization sensitivities in a swirling flow. (March 2017) - Foley, Christopher; Chterev, Ianko; Noble, Bobby; Seitzman, Jerry; Lieuwen, Tim
A variety of different flame configurations and heat release distributions exist in high swirl, annular flows, due to the existence of inner and outer shear layers as well a vortex breakdown bubble. Each of these different configurations, in turn, has different thermoacoustic sensitivities and influences on combustor emissions, nozzle durability, and liner heating. This paper presents findings on the sensitivities of the outer shear layer- stabilized flames to a range of parameters, including equivalence ratio, bulkhead temperature, flow velocity, and preheat temperature. There is significant hysteresis for flame attachment/detachment from the outer shear layer and this hysteresis is also described. Results are also correlated with extinction stretch rate calculations based on detailed kinetic simulations. In addition, we show that the bulkhead temperature near the flame attachment point has significant impact on outer shear layer detachment. This indicates that understanding the heat transfer between the edge flame stabilized in the shear layer and the nozzle hardware is needed in order to predict shear layer flame stabilization limits. Moreover, it shows that simulations cannot simply assume adiabatic boundary conditions if they are to capture these transitions. We also show that the reference temperature for correlating these transitions is quite different for attachment and local blow off. Finally, these results highlight the deficiencies in current understanding of the influence of fluid mechanic parameters (e.g. velocity, swirl number) on shear layer flame attachment. For example, they show that the seemingly simple matter of scaling flame transition points with changes in flow velocities is not understood.